2019
DOI: 10.3390/su11051384
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sustainable Development by Tourists’ Place Emotion: Analysis of the Multiply Mediating Effect of Attitude

Abstract: Place emotion is an important factor in studying the behavioral intention of tourists. Based on the planning behavior theory and goal-oriented behavior model, this article combines the actual situation of rural tourist, expands the behavioral theory, and constructs the tourist behavior of place emotion. This paper takes the World Cultural Heritage Sites Xidi and Hongcun as research cases and uses Structural Equation Modeling (SEM) research methods. The results indicate that the constructed behavior intention o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 41 publications
2
26
1
Order By: Relevance
“…Some authors [47] have found that people with greater emotional well-being are more likely to express positive attitudes towards purchasing sustainable products. Other researchers [48] have found that emotion has a positive influence on tourism attitude, whereas attitude has a partial mediating effect on emotion. Respondents may use a series of positive, negative, or mixed emotional words to express their attitudes towards value perceptions of tourism products during interviews [49].…”
Section: Effects Of Emotion On Behaviormentioning
confidence: 88%
“…Some authors [47] have found that people with greater emotional well-being are more likely to express positive attitudes towards purchasing sustainable products. Other researchers [48] have found that emotion has a positive influence on tourism attitude, whereas attitude has a partial mediating effect on emotion. Respondents may use a series of positive, negative, or mixed emotional words to express their attitudes towards value perceptions of tourism products during interviews [49].…”
Section: Effects Of Emotion On Behaviormentioning
confidence: 88%
“…In summary, prior studies mainly interpreted the GOSC consumers' decision-making process from the cognitive and rational perspective and indicated that consumers are likely to carefully evaluate risks and benefits of consumption in GOSC. In addition, these findings also suggested that the festival atmosphere of GOSC usually arouse people's emotion of excitement and pleasure, and such an emotion determined consumers' shopping decisions [15][16][17]. However, this strand of literature is scarce, and few studies have explored the roles of cognition and emotional state within the decision-making process of consumers based on an integrated theoretical framework.…”
Section: Research Background Of Goscmentioning
confidence: 99%
“…Researchers also might investigate such measurements design using different analytical methods such as SEM using partial least square [48]. Second, previous studies in sustainable tourism asserted the importance of some mediators that clearly explained travelers' sustainable decision-making process and behaviors (e.g., satisfaction, emotions, commitment) [1,40,49]. Yet, the present research did not include such crucial mediators that possibly maximize the effect of independent variables on the outcome variables.…”
Section: Discussionmentioning
confidence: 87%